1988
DOI: 10.1007/bf00248750
|View full text |Cite
|
Sign up to set email alerts
|

Negative cortical DC shifts preceding and accompanying simultaneous and sequential finger movements

Abstract: Cortical DC shifts preceding and accompanying the execution of five different bimanual motor tasks were analysed in 20 subjects. All tasks required repetitive flexions and extensions of the two forefingers for a period of at least six seconds. The temporal and spatial structures organization varied in the different tasks: (1) Simultaneous agonistic performance (forefinger flexion on both sides), (2) simultaneous antagonistic performance (e.g. flexion of the right, extension of the left forefinger), (3) sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Studies on cortical DC shifts revealed that the amplitudes of potentials in the medial frontal cortex were larger when motor tasks involved (1) sequential movements, (2) memorized motor sequence, and (3) bimanual coordination [4,11]. Subsequent studies [28,34,36] extended these observations further. Of particular interest is the finding [35] that a large DC potential shifts were recorded when subjects were tapping different rhythms bimanually.…”
Section: Sma Neurons In Organizing Temporal Sequences Of Multiple Movmentioning
confidence: 88%
“…Studies on cortical DC shifts revealed that the amplitudes of potentials in the medial frontal cortex were larger when motor tasks involved (1) sequential movements, (2) memorized motor sequence, and (3) bimanual coordination [4,11]. Subsequent studies [28,34,36] extended these observations further. Of particular interest is the finding [35] that a large DC potential shifts were recorded when subjects were tapping different rhythms bimanually.…”
Section: Sma Neurons In Organizing Temporal Sequences Of Multiple Movmentioning
confidence: 88%
“…The bereitschaftspotential (BP) or motor readiness potential is a negative-going deflection in the EEG centered around the dorsal motor and mediodorsal areas before a motor response. It is believed to reflect the preparatory set and intention to act (Lang et al, 1988). This potential can begin up to a second or more before a self-paced act.…”
Section: Methodsmentioning
confidence: 99%
“…The specific ERP feature that we use is the lateralized BP. Neurophysiologically, the BP is well investigated and described [5], [6]. New questions that arise in this context are 1) is the BP observable also in fast motor sequences, and 2) can the lateralization be discriminated on a single-trial basis?…”
Section: B Prediction Of Laterality In Fast Self-paced Motor Commandsmentioning
confidence: 98%